THE INFLUENCE OF TECHNIQUE ON THE PERFORMANCE IN THE SWIMMING EVENTS - Viorel, Bitang (Arena-Journal of Physical Activities, 2014)
The present study aims the theoretical and experimental research regarding the major part of the technical component among junior swimmers. Increasing the efficiency of the educational process requires the establishment of specific aims, of a well objectified and optimized operating plan as well as the selection of the most effective methods and means of operation. The establishment of some training norms as well as the judicial use of the most effective ways and means particular or not for swimming should lead to: - The appropriate acquiring from the point of view of the technique of the four swimming procedures - The development of driving skills - The demonstration of the validity of the methods used and the applicability of some tests in order to follow the qualitative development of driving skills. Implementing systematically a model of professional algorithms for learning, consolidation and improvement from a technical point of view, during an educational year, the sportsmen will obtain superior results.